ANALYSIS OF EMPLOYEE DEVELOPMENT STRATEGIES AND CORPORATE STARTEGIES TO INCREASE PRODUCTIVITY AND CULINARY COMPETITIVENESS OF GEPREK CHICKEN : Empirical Study on Kafanaa Chicken & Noodles - Ismawati, Lilik; Churiyah, Madziatul (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2023)
This research journal aims to analyze employee development strategies and corporate strategies at the Kafanaa Chicken and Mie restaurant. The research method used is a qualitative empirical study with data collection techniques through interviews and observation. The results of this research show that employee development strategies and corporate strategies are effective in helping Kafanaa Chicken & Mie to increase productivity and culinary competitiveness. Based on the results of this research, employee development strategies and corporate strategies are effective in increasing productivity and competitiveness, so it is highly recommended for businesses operating in the culinary industry to implement employee development strategies and corporate strategies